Effect of Herbal Preparations on Immune Response in Broilers immunized with Gumboro Disease Vaccine - Abdulla Sheehan; A.M.Al-Aalim; Nawar Ali Jasim (The Indian Veterinary Journal, 2026)
This study aimed to know the effect of three commercial products, namely, Sumerfeed, Oregofarm and garlic, which are routinely used in poultry farms, on enhancing immunity. Seventy-five one-day-old broiler chicks were used and divided into five equal groups. Three groups were treated with Sumerfeed, Oregofarm, and garlic, respectively and vaccinated against Infectious Bursal Disease (IBD). The fourth group was left as a positive control group without any treatment but vaccinated against IBD, and the fifth group was left as a negative control that was neither treated nor vaccinated. Antibodies against IBD, in addition to CD4+ and CD8+ T-cell levels, were estimated using commercial ELISA kits. The results of the study showed a high efficiency with Sumerfeed and Oregofarm, followed by garlic in enhancing immune response against the IBD vaccine. This study showed increasing of specific antibodies against IBD with increasing levels of CD4+ and CD8+ cells.